ПРОБЛЕМА ФОРМУВАННЯ ХУДОЖНЬО-ПРОФЕСІЙНИХ УМІНЬ У ПРОЦЕСІ ПІДГОТОВКИ ВЧИТЕЛІВ ОБРАЗОТВОРЧОГО У МИСТЕЦТВА У ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДАХ (Педагогіка вищої та середньої школи, 2009)
Thu article is devoted a question of training future visual arts teachers. Here are (unsized features of formation art abilities in the process of professional students training in visual- pedagogical specialities.